Differential and integral calculus: from the fedathi sequence to adavanced mathematical thinking (Research, Society and Development, 2020)
The objective of this article is to present a research focused on the teaching of Calculus, motivated by the difficulties shown by the students, especially in the Derivatives and Integrals contents. Therefore, it seeks to understand whether the use of the Fedathi Sequence (FS) teaching methodology by teachers can develop aspects of Advanced Mathematical Thinking (AMT) in the construction of students reasoning. The methodology took place with an initial literature review followed by a case study with subjects from a study group at the State University Vale do Acaraú, and for analysis of the results, the categories of the AMT Cognitive Theory, listed in the research development, were observed. The results showed that the change in teaching posture raised other students demands that were noticeable in the mathematical work presented during the activities performed.